Case report of concurrent ulcerative colitis and bilateral breast cancer: a literature review of the bidirectional association between autoimmune diseases and breast cancer - Qi, Xiao; Zhang, Miao; Zhu, Jinhong; Wang, Huaqing (Frontiers in Oncology, 2025)
A 58-year-old female patient with bilateral breast cancer developed unexpected hematochezia at a frequency of approximately 10 episodes per day following adjuvant chemotherapy, with the emergency endoscopy reporting superficial ulcers throughout the entire colon, suggesting a diagnosis of ulcerative colitis (UC). Given the absence of preexisting autoimmune history or detectable autoantibodies, we supposed that the onset of UC was closely related to the chemotherapy. The complex bidirectional relationship between autoimmune rheumatic diseases and cancer continues to be elucidated. Variations in autoimmune disease type, duration, and specific clinical/laboratory features may modulate cancer risk, either increasing or decreasing susceptibility to certain malignancies. These associations could potentially inform type-specific cancer screening strategies. Furthermore, the widespread use of immune checkpoint inhibitors across multiple tumor types, along with their associated inflammatory syndromes, has significant implications for the development and management of autoimmune rheumatic diseases. Herein, we report this case, which could be one of the few bilateral breast cancer cases to be reported with ulcerative colitis, and conducted a literature review of the bidirectional association of breast cancer and autoimmune diseases.